The Impact of Environmental Awareness on Green Product and Green Accommodation Purchasing Behavior: A Study on Domestic Tourists Visiting Antalya Province - Aysen Ercan İştin; Ahmet Özben (Journal of Tourismology)
This study aims to determine whether environmental awareness significantly impacts green product and green accommodation purchasing behavior, and whether green product purchasing behavior significantly influences green accommodation purchasing behavior. Using quantitative research method, this study collected data from 454 people via a survey form. Domestic tourists who visit Antalya constitute the research population. The sample consists of domestic tourists who participate in the study and visit Antalya. The study employed a convenience sampling method, specifically a survey model. Result of the analysis revealed a lowto medium-level relationship between the dimensions of the research variables. Moreover, environmental awareness significantly impacts the purchasing behavior toward green products and green accommodations. Meanwhile, green product purchasing behavior significantly impacts green accommodation purchasing behavior.